How Flash Sale, Product Expiry, And Quality Affect Consumer Purchase Intentions Online On Shopee - Dian Meliantari; Achmad Tarmizi (Journal of Education Technology Information Social Sciences and Health, 2026)
In the digital age, online shopping has become an important part of consumer behavior, thus encouraging businesses to develop strategies that can influence purchasing decisions. This study aims to analyze the influence of flash sales, product expiration date information, and product quality on consumer purchase intent on e-commerce platforms. Flash sales, which are characterized by time-limited discounts, are widely used to create a sense of urgency and encourage impulse purchases. Meanwhile, expiration date information is crucial in building consumer trust, especially for perishable products, as it relates directly to perceptions of safety and reliability. But there are also consumers who target products that are close to their expiration date because the price is usually slammed very cheaply. Product quality, which includes tangible attributes as well as consumer perceptions, remains a key factor in ensuring consumer satisfaction and loyalty. The provision of high-quality products and clear expiration date information, combined with timely flash sales, can strengthen trust, encourage quick purchases, and build consumer loyalty in the competitive e-commerce market. This study uses a quantitative approach with a sample of 100 active e-commerce users. The results of the study show that Partially Flash Sale, Product Expiry and Quality have a significant effect on Purchase Intention (Y).